The Real Exchange Rate and Economic Growth: Some Observations on the Possible Channels - Martín Rapetti (University of Massachusetts, Department of Economics, 2013)
A recent body of empirical research has documented a strong association between the level and volatility of the RER and economic growth. This research has relied on a variety of econometric techniques applied to large cross-country data sets. Although the documented positive effects of both RER competitiveness and stability on growth appear to be robust, it is still unclear what the mechanisms driving these associations are. Several explanations have been proposed, but their theoretical examination and empirical validation is still in an infant stage. I analyze the mechanisms that have been proposed and evaluate them in light of the documented empirical evidence. My reading is that two of them adjust to the empirical findings best: the financial globalization channel and the tradable-led growth channel. I conclude that since these mechanisms are not mutually exclusive, both might have some explanatory power.
Keywords: O24; F43; F31; O11; 330; real exchange rate; growth; development; growth econometric